Antimalarials: Pre-Clinical development update - Bala, Moumita; Lahiry, Sandeep; Choudhury, Shouvik; Mukherjee, Ayan; Bhunya, Prajesh Kiran; Chowdhury, Koustuv; Sinha, Rajasree (Asian Journal of Medical Sciences, 2017)
Diverse strategies exist for the development of novel antimalarials drug to tackle the increasing incidence of artemisin resistance. New molecules have been developed which hold a promise to cater to this unmet need. We discuss few drugs currently under pre-clinical development that have shown encouraging results. Asian Journal of Medical Sciences Vol.8(5) 2017 1-3